342 THE DISCRIMINATORY VALUE OF ANP-LED CGA ON PATIENT REPORTED SYMPTOMS AND IMPACT ON CARERS: A CROSS-SECTIONAL STUDY. (25th October 2022) - Mannion, E; Murphy, R; Robinson, S; Waters, R; Donnell, MO; Walsh, T; Geoghegan, J; Conry, M; Canavan, M
Abstract: Background: Comprehensive Geriatric Assessment (CGA) is a cornerstone in geriatric care. Objective findings from CGA may differ to patient and carer reported symptoms. This study compared patient reported symptoms with objective metrics collected during CGA and explored the relationship with carer burnout. Methods: Cross-sectional study of patients attending an Advanced Nurse Practitioner (ANP)-led integrated care clinic. Patient-reported geriatric syndromes included low mood, memory concerns, incontinence, falls or dizziness. CGA metrics collected included Barthel Index, Lawton IADLs, MOCA scores, Geriatric depression scale scores, Rockwood Clinical Frailty Scale (CFS) scores and presence or absence of carer burnout. Descriptive statistics were used to compare the relationship between these variables and logistic regression explored the magnitude of association with carer burnout. Results: We reviewed 99 CGAs over three months. Median age was 81 (IQR 75–86) with 62% female. Cognitive impairment was present in 96% of patients. Self-reported memory trouble was associated with lower MOCA scores (9 vs 23, p < 0.001) and the presence of dizziness was associated with an increased prevalence of falls (89% vs 24%, < 0.001). The presence of incontinence and functional dependency on IADL were both associated with carer strain and a larger magnitude of association with carer strain was seen with increasing frailty (OR 13.7, 95% CI 3.8-58.8 for moderate to severe frailty) than moderate to severe cognitive impairment (OR 8, 95% CI 3.0–24.1) Conclusion: Older people reported a wide range of symptoms often subtle, some of which are unmasked during CGA. The resultant frailty syndromes often represent increasing degrees of functional impairment impacting on patient and carer quality of life. Striking the balance between patient reported symptoms and objective measurement is important to allow individualised care pathways to be developed as well as highlighting patients at risk of functional and cognitive decline.